DESIGN PUBLISHING SERVICE APPLICATIONS ARCHITECTURE LICENSE WITH ONE ROOF IN DISPERINDAG CITY OF PALANGKARAYA - Anggriawan, Adventus; Supriyanto, Antok; Arifin, Mochammad (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Disperindag city of Palangkaraya is the city agency had authority to serve and publish such a license, license trading business (SIUP), the business place licence of letter (SITU), licence billboard nuisance or hiring order (HO), tourism licence, construction services business licence (SUJK), and the building permit licence (IMB) city of Palangkaraya in central Kalimantan. Currently the ministry of creation permission on Disperindag city of Palangkaraya was still using document based and manual systems resulting in the creation of a permit being long and make the applicant back and forth to take care of permission to Disperindag. Based on the above problems then proposed the application of service permit issuance with the concept of one stop. Web based application and services made onlinethe applicant need not commute comes to Disperindag for verification of data documents. With the application ministry publishing permit with the concept of one stop this increasing service on Disperindag city of Palangkaraya. The output can be generated in the form of issuance of licence trading business, the business place licence of letter, and permits installation of the billboard. Keywords: One stop service, the issuance of permit